Pengembangan Media PASAKA (Papan Kosakata) Pada Pembelajaran Bahasa Indonesia Untuk Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas 2 Sekolah Dasar - Kartika , Dea; Robiatul Munajah (Global Action and Education for Society, 2026)
The lack of interest in reading and innovation in learning media at SDN Pancoran 03 has resulted in low student interest and understanding of Indonesian language subjects. This study aims to develop PASAKA (Vocabulary Board) learning media to develop early reading skills, to determine the results of its development, and to measure the effectiveness of its use in Indonesian language learning. The method used is Research and Development with the ADDIE model which includes analysis, design, development, implementation, and evaluation. The research subjects were 24 2nd grade students of SDN Pancoran 03. The validation results from media experts obtained 94%, linguists 90%, and material experts 98% with each category